Psychological status of TMD patients, orthodontic patients and the general population during the COVID-19 pandemic. Issue 1 (2nd January 2021) - Wu, Yange; Xiong, Xin; Fang, Xinyi; Sun, Wei; Yi, Yating; Liu, Jin; Wang, Jun
ABSTRACT: Confronting the outbreak of COVID-19, this cross-sectional study was aimed to assess psychological status of temporomandibular disorders (TMD) patients, orthodontic patients and the general population in China during the pandemic. An online anonymous questionnaire was developed in Chinese, including the individual background information, the perception of the epidemic, and level of anxiety and depression through Kessler Psychological Distress Scale (K10). The respondents were divided into ORTHO group, TMD group and Control group. Descriptive analysis and multiple linear regression modelling were performed. In total, 1241 valid questionnaires were collected, covering 587 orthodontic patients and 220 TMD patients. It is shown that the overall mental health is not quite optimistic during the COVID-19 pandemic with the mean score of K10 being 18.65. TMD patients have higher level of anxiety and depression than orthodontic patients as well as the general population. Younger age, female gender, having close contact with individuals from Hubei province, higher self-rated infection possibility, concern about psychological barriers and distrust are negatively affecting patients' psychological status. Mental health care should be emphasized when hospitals and clinics reopen after the COVID-19 pandemic, especially to patients with these relevant characteristics.